2022
DOI: 10.3390/molecules27010260
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Bromelain-Derived Peptide Potentially Restrains the Attachment of SARS-CoV-2 Variants to hACE2: A Pharmacoinformatics Approach

Abstract: Before entering the cell, the SARS-CoV-2 spike glycoprotein receptor-binding domain (RBD) binds to the human angiotensin-converting enzyme 2 (hACE2) receptor. Hence, this RBD is a critical target for the development of antiviral agents. Recent studies have discovered that SARS-CoV-2 variants with mutations in the RBD have spread globally. The purpose of this in silico study was to determine the potential of a fruit bromelain-derived peptide. DYGAVNEVK. to inhibit the entry of various SARS-CoV-2 variants into h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 85 publications
(107 reference statements)
0
16
0
Order By: Relevance
“…Viruses with mutations in their genomes will dominate the population, regardless of their impact on viral fitness [ 7 ]. According to the Centers for Disease Control and Prevention (CDC), SARS-CoV-2 variants are classified into four classes, namely: “variants being monitored (VBM)”, “variants of interest (VOI)”, “variants of concern (VOC)”, and “variants of high consequence (VOHC)” ( ; accessed on 31 January 2022) [ 15 , 16 , 17 ]. VBM are variants that have been linked to more severe illness or increased transmission, but are no longer detectable or are circulating at extremely low levels.…”
Section: Sars-cov-2 Mutation Results In the Emergence Of Various Vari...mentioning
confidence: 99%
“…Viruses with mutations in their genomes will dominate the population, regardless of their impact on viral fitness [ 7 ]. According to the Centers for Disease Control and Prevention (CDC), SARS-CoV-2 variants are classified into four classes, namely: “variants being monitored (VBM)”, “variants of interest (VOI)”, “variants of concern (VOC)”, and “variants of high consequence (VOHC)” ( ; accessed on 31 January 2022) [ 15 , 16 , 17 ]. VBM are variants that have been linked to more severe illness or increased transmission, but are no longer detectable or are circulating at extremely low levels.…”
Section: Sars-cov-2 Mutation Results In the Emergence Of Various Vari...mentioning
confidence: 99%
“…Tallei et al used the HawkDock server to evaluate the BFE to understand the attachment of a fruit-derived small peptide. It has been noted that the small peptide can restrain the attachment of variants of SARS-CoV-2 RBD to hACE2 ( Tallei et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Tallei et al [53] revealed that a fruit bromelain-derived peptide DYGAVNEVK interacts with several critical SARS-CoV-2 spike glycoprotein receptor-binding domain binding residues responsible for the adhesion of the receptor-binding domain to human angiotensin-converting enzyme 2 receptors and restrains its attachment. Akhter et al [54] revealed that bromelain and acetylcysteine (BromAc) have synergistic action against glycoproteins of SARS-CoV-2 by breakage of its glycosidic linkages and disulfide bonds.…”
Section: Bromelain and Covid-19mentioning
confidence: 99%